The Role of Estrogen and Progesterone Fluctuations in the Pathogenesis of Postpartum Psychosis: A Neurobiological Review - Taufan, Wa Ode Sri Apriani; Khaerina, Ilma; Japari, Agus (Journal La Medihealtico, 2026)
Postpartum psychosis is an acute psychiatric disorder characterized by rapid onset following childbirth, posing significant risks to both maternal and neonatal safety. Its underlying mechanisms remain incompletely understood; however, fluctuations in reproductive hormones particularly estrogen and progesterone are strongly implicated in its pathogenesis. The abrupt decline of these hormones after delivery may disrupt neurotransmitter systems, especially dopaminergic and GABAergic pathways, thereby precipitating neurobiological imbalance in vulnerable individuals. This study employs a literature review method using a narrative review approach, drawing upon databases such as PubMed, ScienceDirect, and Google Scholar, complemented by manual searches. Following the PRISMA framework, a total of 20 articles met the inclusion criteria and were systematically analyzed. The findings indicate that estrogen demonstrates a more consistent association with psychotic symptomatology, whereas progesterone exerts its effects primarily through its metabolite, allopregnanolone, which modulates the GABAergic system. In addition, genetic predisposition, sleep disturbances, and alterations in neuroplasticity contribute to the condition. Postpartum psychosis therefore emerges as a multifactorial disorder resulting from the complex interplay between hormonal fluctuations and underlying neurobiological vulnerability.